Deciphering the role of metabolites and phytohormones in plant resilience to drought and herbivory - Sahu, Monika; Giri, Ashok P. (Plant Stress, 2025)
<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Climate change is expected to result in increased variability in precipitation and more frequent outbreaks of insect pests. Thus, it is important to understand how plant-environment interactions are affected by both abiotic and biotic stresses. Water is essential for plant growth, development and interactions with other organisms, including insects. This review synthesizes current studies on the impact of drought and herbivore defense mechanisms and associated metabolic changes in plants. Severe drought can enhance plant tolerance to herbivores by promoting escape strategies whereas mild or intermittent drought may benefit insects by increasing nutrient availability. We discuss how plants adjust their metabolism to mitigate the effects of combined stresses. We further highlight the role of hormonal signaling pathways, such as <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/abscisic-acid" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">abscisic acid, <a class="topic-link" href="https://www.sciencedirect.com/topics/biochemistry-genetics-and-molecular-biology/jasmonate" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px; font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">jasmonic acid<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">, salicylic acid and ethylene in coordinating plant responses. Research on metabolic changes accompanying hormonal crosstalk involved in managing multiple stresses is still emerging. The available evidence suggests that the outcome of drought and herbivory varies depending on factors such as stress intensity, duration, plant-herbivore species, and insect-feeding guilds. We propose open questions and anticipate further advances in molecular understanding of plant resilience to combined stresses such as drought and herbivory in the near future.